Resolution of Uncontrolled Type 2 Diabetes after Laparoscopic Truncal Vagotomy, Subtotal Gastrectomy, and Roux-en-Y Gastrojejunostomy for a Patient with Intractable Gastric Ulcers. (3rd November 2012) - Tait, Laura F.; Ortega, Gezzer; Tran, Daniel D.; Fullum, Terrence M.
Abstract : Background . Laparoscopic Roux-en-Y gastric bypass (LRYGB) has been shown to be an effective treatment for type 2 diabetes mellitus (T2DM) in patients with morbid obesity. However, it is unclear just how effective the LRYGB procedure is on T2DM for patients with BMI less than 35 kg/m 2 . We report one obese patient with T2DM who did not meet the current NIH criteria for morbid obesity surgery. This patient underwent a laparoscopic truncal vagotomy, subtotal gastrectomy, and Roux-en-Y gastrojejunostomy for intractable gastric ulcers and subsequently had full resolution of her T2DM. Methods . A 48-year-old patient with a BMI of 34.6 kg/m 2 underwent a laparoscopic truncal vagotomy, subtotal gastrectomy, and Roux-en-Y gastrojejunostomy for intractable gastric ulcers. The patient was seen 3 months preoperatively, followed for 24 months postoperatively, and evaluated for postoperative complications, weight loss, and improvement in comorbidities. Results . The patient had no postoperative surgical complications. Her BMI decreased from 34.6 kg/m 2 to 22.3 kg/m 2 by 24 months postoperatively. Significant improvements in her fasting blood glucose levels were seen 10 days postoperatively from a preoperative level of 147 mg/dl to 97 mg/dl. Conclusion . Patients with a BMI less than 35 kg/m 2 and uncontrolled T2DM may benefit from a laparoscopic Roux-en-Y gastric bypass.